Les paramètres évidentiels, inférentiels et modaux appliqués à l’étude de must épistémique - Yves Bardière (Anglophonia)
This study focuses on the modal and evidential values of must / devoir. The major difficulty is that evidentiality is not clearly grammaticalized neither in English nor French, unlike Amerindian languages such as Tuyuca or Bosavi. However new theories have emerged showing that not only modal but also evidential values can be conveyed by modal auxiliaries, especially those expressing an epistemic meaning. Another problem is that most analyses have generated some conceptual confusion, which makes it difficult to assess the respective roles of evidentiality and modality and the possible relationship between the two. For instance inferential evidentiality and epistemic modality are often used interchangeably. This study therefore aims at providing the reader with a simple method which consists in applying the Guillaumian concept of notional chronology to three notions, evidentiality, inference and modality. These notions are both distinct and closely interconnected and inference plays a key role in this cause-effect relationship. This relationship shows that if modality implies evidentiality, evidentiality does not automatically lead to modality. It ultimately makes it possible to shed some light on one of the major questions of today’s research: is evidentiality coded or not in the semantic value of epistemic modal auxiliaries?